2013
DOI: 10.1097/dcr.0b013e3182839824
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable Synthetic Plug in the Treatment of Anal Fistulas

Abstract: In patients with cryptoglandular anal fistulas, the use of a bioabsorbable synthetic plug provided a high rate of healing without causing fecal incontinence or other major adverse effects. Larger and randomized studies of this treatment are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…The Gore Bio-A fistula plug (Gore Medical, Flagstaff, AZ) is a synthetic bioabsorbable scaffold that acts in a manner similar to the Surgisis plug, but for a reportedly cheaper price, and with the addition of several "tentacles" that can be removed or adjusted in a fashion tailored to the size and number of fistula tracts. 60 Initial primary healing with this plug was reported at 69%, 61 but a subsequent multicenter case series reported a 12-month healing rate of 49%. 60 Overall, the AFP appears to be an acceptable approach to complex anal fistulas, as it is generally well tolerated with minimal side effects.…”
Section: Fistula Plugmentioning
confidence: 99%
“…The Gore Bio-A fistula plug (Gore Medical, Flagstaff, AZ) is a synthetic bioabsorbable scaffold that acts in a manner similar to the Surgisis plug, but for a reportedly cheaper price, and with the addition of several "tentacles" that can be removed or adjusted in a fashion tailored to the size and number of fistula tracts. 60 Initial primary healing with this plug was reported at 69%, 61 but a subsequent multicenter case series reported a 12-month healing rate of 49%. 60 Overall, the AFP appears to be an acceptable approach to complex anal fistulas, as it is generally well tolerated with minimal side effects.…”
Section: Fistula Plugmentioning
confidence: 99%
“…In their analysis of the success rates of biomaterial plugs in a homogeneous group of patients (trans-sphincteric fistulae with cryptic etiology), Heydri et al demonstrated a 69% efficacy rate in a 12-month follow-up period [10]. Similar results were obtained by Ratto et al who observed a success rate of more than 72% [11].…”
Section: Introductionmentioning
confidence: 60%
“…The synthetic plug does not require rehydration before use. Heydari et al, 76 in their retrospective study on cryptoglandular, transsphincteric, and intersphincteric AF treated by bioabsorbable synthetic fistula plug, reported an overall healing rate at 12 months of 69.3% confirmed by ERUS. Among patients that healed, 24.2% had healed by 3 months, 63.6% by 6 months, and 12.1% by 12 months.…”
Section: Bioabsorbable Synthetic Fistula Plugmentioning
confidence: 98%
“…The polymer scaffold is replaced by a layer of new tissue that reinforces the repair. 76 The synthetic plug device consists of a PGA/TMC disk to which several narrow PGA/TMC tubes are attached. At the time of insertion, the plug can be tailored to fit and fill the specific fistula both by trimming the diameter of the disk and by removing one or more of the tubes.…”
Section: Bioabsorbable Synthetic Fistula Plugmentioning
confidence: 99%